Desain Pengembangan Kerjasama Kelembagaan dalam Peningkatan Profesionalisme Civitas Akademika di Fakultas Ilmu Tarbiyah Dan Keguruan (FITK) IAIN Surakarta - Muhammad Munadi; Retno Wahyuningsih; Khuriyah Khuriyah (Kelola: Jurnal Manajemen Pendidikan, 2019)
This research aims to understand the reality of cooperation management, the reality of cooperation development and development design of institutional cooperation on the improvement of civitas academic professionalism in IAIN Surakarta. This research is categorized as non-positivistic research in which in its analysis, it emphasizes more on the words of the object under study. This study was located in Faculty of Education and Teacher Training since it has a lot of spaces for profession development, especially a space for Field Experience Practice (Praktek Pengalaman Lapangan / PPL) program that nearly covers madrasah/schools in eks-Karesidenan Surakarta, a space for Fieldwork Study (Kuliah Kerja Lapangan), and madrasah/schools empowerment activity. The subject of this research is 4 heads of department, 3 heads of deanship and 3 rectorate officials. Data collection technique is using interview, observation, and documentation. Data validity technique is using source and method triangulation. Data analysis is using interactive analysis model. The result of this research shows that: The reality of cooperation management is still “top down” when it is related to the draft planning of collaboration paper. The reality of cooperation development which was started from cooperation without legal protection develops into the one with legal protection. Cooperation development design is developed through user mapping, strengthen the cooperation with school partners which focuses not only on PPL implementation but also on “give and take” activity which has yet happened between madrasah/schools and faculties in IAIN Surakarta.